The impacts of particle size on starch structural characteristics and oil-binding ability of rice flour subjected to dry heating treatment. (1st November 2019) - Zhou, Wanxia; Song, Jingjing; Zhang, Bin; Zhao, Lei; Hu, Zhuoyan; Wang, Kai
Highlights: Rice flour with smaller size had lower gelatinization temperatures and enthalpy change of starch. Dry heating did not change the crystalline type of starch, while it reduced starch crystallinity. Rice flour with smaller size displayed higher hydrophobicity and oil-binding ability. Abstract: As a main starch source in human diet, milled rice flour has been widely used in various foods, and its particle size may impact the quality of final products. This study investigated the effects of particle size on starch structure and oil-binding ability of rice flour subjected to dry heating treatment. The results showed that fine fraction of rice flour had lower starch content. All samples showed A-type crystalline structure of starch, and this crystalline type was not changed by dry heating treatment, although the crystallinity was reduced. Rice flour with smaller size exhibited lower starch gelatinization temperatures and enthalpy change, and displayed higher hydrophobicity and oil-binding ability. The hydrophobicity of rice flour was improved by dry heating as observed from the increased three-phase contact angle, attributing to elevated surface hydrophobicity of rice protein. These results will provide guidance for developing functional ingredients with improved oil-binding ability for non-gluten foods.